90=(x-2)(y-1.5)

Simple and best practice solution for 90=(x-2)(y-1.5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=(x-2)(y-1.5) equation:


Simplifying
90 = (x + -2)(y + -1.5)

Reorder the terms:
90 = (-2 + x)(y + -1.5)

Reorder the terms:
90 = (-2 + x)(-1.5 + y)

Multiply (-2 + x) * (-1.5 + y)
90 = (-2(-1.5 + y) + x(-1.5 + y))
90 = ((-1.5 * -2 + y * -2) + x(-1.5 + y))
90 = ((3 + -2y) + x(-1.5 + y))
90 = (3 + -2y + (-1.5 * x + y * x))
90 = (3 + -2y + (-1.5x + xy))

Reorder the terms:
90 = (3 + -1.5x + xy + -2y)
90 = (3 + -1.5x + xy + -2y)

Solving
90 = 3 + -1.5x + xy + -2y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.5x' to each side of the equation.
90 + 1.5x = 3 + -1.5x + xy + 1.5x + -2y

Reorder the terms:
90 + 1.5x = 3 + -1.5x + 1.5x + xy + -2y

Combine like terms: -1.5x + 1.5x = 0.0
90 + 1.5x = 3 + 0.0 + xy + -2y
90 + 1.5x = 3 + xy + -2y

Add '-1xy' to each side of the equation.
90 + 1.5x + -1xy = 3 + xy + -1xy + -2y

Combine like terms: xy + -1xy = 0
90 + 1.5x + -1xy = 3 + 0 + -2y
90 + 1.5x + -1xy = 3 + -2y

Add '-90' to each side of the equation.
90 + 1.5x + -90 + -1xy = 3 + -90 + -2y

Reorder the terms:
90 + -90 + 1.5x + -1xy = 3 + -90 + -2y

Combine like terms: 90 + -90 = 0
0 + 1.5x + -1xy = 3 + -90 + -2y
1.5x + -1xy = 3 + -90 + -2y

Combine like terms: 3 + -90 = -87
1.5x + -1xy = -87 + -2y

Reorder the terms:
87 + 1.5x + -1xy + 2y = -87 + -2y + 87 + 2y

Reorder the terms:
87 + 1.5x + -1xy + 2y = -87 + 87 + -2y + 2y

Combine like terms: -87 + 87 = 0
87 + 1.5x + -1xy + 2y = 0 + -2y + 2y
87 + 1.5x + -1xy + 2y = -2y + 2y

Combine like terms: -2y + 2y = 0
87 + 1.5x + -1xy + 2y = 0

The solution to this equation could not be determined.

See similar equations:

| 12/5=x/45 | | (4i)(-8+8i)= | | 5.3x=4.1x+5.76 | | 2.5h+.5(h-1)=-12.5 | | 5x-9=-3x+12+5x | | 7/12=x60 | | 1/8x-9=17 | | 3x+6=8x-49 | | 2x-3(5-3x)=7x+3 | | .3+.2(g+7)=1.5 | | -0.005q^2+2.5q=300 | | 11*y=77 | | 3x+6=10x+3 | | Hg(x)=2g(x) | | (5x-1)/x=1 | | -40(-28/3) | | .1(f-7)+.05f=.8 | | -(x+3)=2+7 | | log32b=-1/4 | | 42=3w-9 | | 3x+2(3)=4 | | 5-3x=-4[3(x+2)-1] | | 7d=4+6d | | 2(-14/3)-40 | | 9y+4=8y-5 | | -2v/9=-12 | | 8=y/25.6 | | .4(e+5)-.3e=17 | | (5x-1)/1=1 | | 8(4-x)=4(x+5) | | 3x-6.2=14.2 | | -8d=-9d+7 |

Equations solver categories